STRENGTHENING OF COASTAL SANDS BY USING GELLAN GUM AND OPTIMIZED MICROBIALLY INDUCED CALCITE PRECIPITATION - ASHRAF, MUHAMMAD SOHAIL (2019)
Excessive effluent ammonia limits the potential ground improvement applications of the Microbially Induced Calcite Precipitation (MICP) process due to its harmful environmental consequences. Alternatively, innocuous biopolymers are being researched for strengthening soils, but their hydrophilic nature reduces their ground improvement potential overtime. This research not only optimized the current MICP process (by reducing the excessive effluent ammonia) for strengthening coastal sand deposits by using sea water but also conducted the first laboratory scale study of using gellan gum biopolymer for strengthening these sands using sea water. Statistically optimized trials of MICP treatment were developed by using Response Surface Methodology (RSM) for the treatment of sand columns. The Unconfined Compressive Strength (UCS) results of these treated columns were fed into the developed statistical model for further optimization of influent concentrations (urea = 0.01 M  0.10 M; CaCl2= 0.00 M  0.05 M).